∫ − 1 1 ( d x 7 0 0 d 7 0 0 [ ( x 2 − 1 ) 7 0 0 ] ) k = 0 ∑ 4 ( − 1 ) k ( 8 k ) ( 1 6 − 2 k 8 ) x 8 − 2 k d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
It is easy to see that
d x 7 0 0 d 7 0 0 [ ( x 2 − 1 ) 7 0 0 ] = 2 7 0 0 7 0 0 ! P 7 0 0 ( x )
and
k = 0 ∑ 4 ( − 1 ) k ( 8 k ) ( 1 6 − 2 k 8 ) x 8 − 2 k = 2 8 P 8 ( x )
where P l ( x ) stands for the l -th Legendre Polynomial. As we know
∫ − 1 1 P m ( x ) P n ( x ) d x = 2 m + 1 2 δ m , n
is the normalization integral, where δ m , n stands for the Kronecker delta. Now it is easy to notice that if we denote the original integral by O we get
O = 2 7 0 8 × 7 0 0 ! × ∫ − 1 1 P 7 0 0 ( x ) P 8 ( x ) d x = 2 7 0 8 × 7 0 0 ! × 0 = 0